2023
DOI: 10.3389/fmars.2023.1017378
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a microbiosphere to clean up the ocean – inspiration from the plastisphere

Abstract: Plastic is a ubiquitous material that has become an essential part of our lives. More than one hundred million tons of plastic has accumulated in the world’s oceans as a result of poor waste management. This plastic waste gradually fragments into smaller pieces known as microplastics and nanoplastics. These small plastic particles can cause significant damage to marine ecosystems, and negatively impact human health. According to a recent review of international patents, the majority of ocean-cleaning invention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Provided the authors are well versed in their fields and choose a subject matter that is relevant and in alignment with the current research trends, the writing of a review or perspective article is a straightforward process. A perspective article relating to marine plastic waste that was published recently took me only three weeks to write from the conception of the idea to the final submitted version and that was without the assistance of text generators or literature analysis software (Alnahdi et al, 2023). With AI-based tools, this entire writing process could be expedited and-upscaled with powerful qualitative data analysis software and text-generating applications designed to survey the literature and rapidly generate textual material.…”
Section: Non-experimental Work Provides a Fast-track Route For Increa...mentioning
confidence: 99%
“…Provided the authors are well versed in their fields and choose a subject matter that is relevant and in alignment with the current research trends, the writing of a review or perspective article is a straightforward process. A perspective article relating to marine plastic waste that was published recently took me only three weeks to write from the conception of the idea to the final submitted version and that was without the assistance of text generators or literature analysis software (Alnahdi et al, 2023). With AI-based tools, this entire writing process could be expedited and-upscaled with powerful qualitative data analysis software and text-generating applications designed to survey the literature and rapidly generate textual material.…”
Section: Non-experimental Work Provides a Fast-track Route For Increa...mentioning
confidence: 99%
“…Poor waste management has resulted in more than one hundred million tons of plastic accumulation across the world's oceans. This plastic waste gradually broken down into smaller pieces called microplastics and nanoplastics which can cause significant damage to marine ecosystems, and negatively impact human health [27].…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…Recently, Alnahdi and coauthors [2023] have presented a concept of engineering a microbial ecosystem, termed the microbiosphere. to design a novel microbial ecosystem engineered as a bioremediation tool to get rid of the ocean of micro-and nanoplastics [27]. Various research has shown that different groups of bacteria, fungi and actinomycetes possess unique property of degrading molecular chains in polymers of both natural and Brazilian Archives of Biology and Technology.…”
Section: Cleaning Of Microplasticsmentioning
confidence: 99%
“…Cleanup efforts are another important component, although they should not be relied upon as the sole solution due to the vastness of the oceans and the difficulties in collecting microplastics [156]. Nonetheless, ongoing initiatives to remove larger plastic debris, which can break down into microplastics, from the environment are important.…”
Section: Solutions and Recommendations For Microplastic Pollutionmentioning
confidence: 99%